Comparative Mapping of the Region of Human Chromosome 7 Deleted in Williams Syndrome - DeSilva, Udaya; Massa, Hillary; Trask, Barbara J.; Green, Eric D. (Genome Research, 1999)
Williams syndrome (WS) is a complex developmental disorder resulting from the deletion of a large (∼1.5–2 Mb) segment of human chromosome 7q11.23. Physical mapping studies have revealed that this deleted region, which contains a number of known genes, is flanked by several large, nearly identical blocks of DNA. The presence of such highly related DNA segments in close physical proximity to one another has hampered efforts to elucidate the precise long-range organization of this segment of chromosome 7. To gain insight about the structure and evolutionary origins of this important and complex genomic region, we have constructed a fully contiguous bacterial artificial chromosome (BAC) and P1-derived artificial chromosome (PAC) contig map encompassing the corresponding region on mouse chromosome 5. In contrast to the difficulties encountered in constructing a clone-based physical map of the human WS region, the BAC/PAC-based map of the mouse WS region was straightforward to construct, with no evidence of large duplicated segments, such as those encountered in the human WS region. To confirm this difference, representative human and mouse BACs were used as probes for performing fluorescence in situ hybridization (FISH) to metaphase and interphase chromosomes. Human BACs derived from the nonunique portion of the WS region hybridized to multiple, closely spaced regions on human chromosome 7q11.23. In contrast, corresponding mouse BACs hybridized to a single site on mouse chromosome 5. Furthermore, FISH analysis revealed the presence of duplicated segments within the WS region of various nonhuman primates (chimpanzee, gorilla, orangutan, and gibbon). Hybridization was also noted at the genomic locations corresponding to human chromosome 7p22 and 7q22 in human, chimpanzee, and gorilla, but not in the other animal species examined. Together, these results indicate that the WS region is associated with large, duplicated blocks of DNA on human chromosome 7q11.23 as well as the corresponding genomic regions of other nonhuman primates. However, such duplications are not present in the mouse.
10.1101/gr.9.5.428